Determination of Effective Parameters for Alpha-Amylase Production in a Modified Rotating Drum Bioreactor - Uygut, M. A.; Tanyildizi, M. A. (Springer Heidelberg, 2018)
In this study, rotating drum bioreactor (RDB), one of the most important bioreactors, used in the solid substrate fermentation was designed by adapting to slurry fermentation. Although conventional RDB is an important microbial production system in terms of preventing heat accumulation and having low shear stress on microorganisms, it is not completely adequate due to heat and mass transfer limitations and low working volume requirement. In order to minimize these problems, ceramic micro-air diffuser was used in modified RDB design. Dissolved oxygen concentration, pH, temperature, oxygen, and carbon dioxide were measured as online. Effects of seven operation parameters such as rotation speed, aeration rate, working volume, diffuser's pore diameter, baffle size, temperature, and inoculum size on the -amylase production in modified RDB were determined by Plackett-Burman design. The rotation speed, aeration rate, and baffle size were statistically significant parameters with low p values () calculated by ANOVA. The maximum value of the specific productivity () was obtained at the high point ( 1) of the significant parameters. As a result, it has been improved an important bioreactor for the cheap enzyme production using agricultural wastes by modified RDB that can be operated at high working volumes.
Keywords: Rotating drum bioreactor; Solid substrate fermentation; Alpha-amylase; Plackett-Burman design